The effect of inhalation aromatherapy using lavender oil on the severity of headache in hemodialysis patients - Zeinab Jamshidi; Shahram Molavynejad; Heshmatollah Shahbazian; Elham Maraghi (Tehran University of Medical Sciences, 2021)
Background & Aim: Dialysis headache is one of the most common complications of hemodialysis and is often a challenge for nephrologists, neurologists and headache specialists. Therefore, this study was conducted to investigate the effect of inhalation aromatherapy using lavender on the severity of headache in hemodialysis patients. Methods & Materials: In this randomized clinical trial, 82 patients from hemodialysis wards of Golestan Hospital in Ahvaz and Shahidzadeh Hospital in Behbahan in 2019 were selected and randomly assigned to either intervention or control groups using the stratified permuted block randomization. For the intervention group, cotton soaked in three drops of lavender essential oil 20% was attached to the collar of the patient and he/she was asked to inhale it for 30 minutes. For the control group, distilled water was used. The intervention was repeated for four weeks (three days per week). The severity of dialysis headache was measured using the Numeric Rating Scale. Results: In the intervention group, both the severity and the frequency of dialysis headache decreased during 12 sessions of aromatherapy, compared to the control group (placebo), and the decrease was statistically significant (P˂0.001). Conclusion: Due to the fact that complementary medicine has increasingly become a part of nursing care, aromatherapy with lavender can be used as a complementary measure reducing the severity and frequency of dialysis headaches. Clinical trial registry: IRCT20190718044263N1